A novel approach to multi-sensor data synchronisation using mobile phones. (1st January 2013) - Wåhslén, Jonas; Orhan, Ibrahim; Lindh, Thomas; Eriksson, Martin
This paper presents a new algorithm for application layer synchronisation of data from multiple sensors arriving to a mobile phone's Bluetooth interface. A system that provides feedback signals to an athlete is one example where it is crucial to synchronise data from several wireless sensors. This paper also discusses synchronisation problems caused by unpredictable Bluetooth transmission performance.